Serum AFU, GGT and TK1 levels in PHC patients and their correlation with clinicopathology and diagnostic value - Gong, Genqiang; Zheng, Kang; Xue, Shunhe; Hou, Jianfeng; Zhang, Qing (Cellular and Molecular Biology, 2020)
To investigate the expression level and clinical significance of fucosidase (AFU), glutamyltranspeptidase (GGT), and thymidine kinase 1 (TK1) in the serum of patients with primary liver cancer (PHC). A total of 135 PHC patients in Baoji Central Hospital from September 2014 to February 2018 were selected as a research group (RG), while 127 healthy subjects were collected as a control group (CG). Enzyme-linked immunosorbent assay (ELISA) was used to detect the AFU, GGT, and TK1 concentrations in serum of the two groups, and the diagnostic value of combined detection of the three for PHC was analyzed. AFU, GGT, and TK1 concentrations in serum of the RG were dramatically higher than those of the CG (P< 0.050). ROC curve analysis showed that the sensitivity of AFU, GGT, and TK1 in the single diagnosis of PHC was 88.00, 94.00, and 66.00% respectively, and the specificity was 68.00, 54.00, and 66.00% respectively. The sensitivity and specificity of the combined diagnosis of PHC were 76.00 and 90.00%, respectively. AFU, GGT, and TK1 concentrations were different in the presence or absence of liver cirrhosis, TNM stage, and tissue type (P< 0.050). AFU, GGT, and TK1 concentrations in PHC patients were dramatically higher than those in healthy people. Combined detection of the three has good diagnostic value for PHC.